Thomas T. Allen. Mongol Imperialism, the policies of the Grand Wan Möngke in China, Russia, and the Islamic Lands, 1251-1259. Berkeley: University of California Press, 1987, 278 pp. - Connelly, Marisela (El Colegio de México, 1992)
-